2020
DOI: 10.1002/jbmr.4484
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Hyperactivation Due to SOCS3 Deletion in Murine Osteocytes Accentuates Responses to Exercise- and Load-Induced Bone Formation

Abstract: Cortical bone develops and changes in response to mechanical load, which is sensed by bone-embedded osteocytes. The bone formation response to load depends on STAT3 intracellular signals, which are upregulated after loading and are subject to negative feedback from Suppressor of Cytokine Signaling 3 (Socs3). Mice with Dmp1Cre-targeted knockout of Socs3 have elevated STAT3 signaling in osteocytes and display delayed cortical bone maturation characterized by impaired accrual of high-density lamellar bone. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“… 23 STAT3 hyperactivation accentuates bone formation on the periosteal surface in response to mechanical stimuli. 24 During both the expansion and relapse periods of our study, STAT3 inactivation reduced migration of periosteal cells to the MPS and suppressed suture widening. Thus, the close relationship between STAT3 and periosteal cells may also impact bone formation in the MPS.…”
Section: Discussionmentioning
confidence: 65%
“… 23 STAT3 hyperactivation accentuates bone formation on the periosteal surface in response to mechanical stimuli. 24 During both the expansion and relapse periods of our study, STAT3 inactivation reduced migration of periosteal cells to the MPS and suppressed suture widening. Thus, the close relationship between STAT3 and periosteal cells may also impact bone formation in the MPS.…”
Section: Discussionmentioning
confidence: 65%
“…Recent studies showed that STAT3 was phosphorylated in response to mechanical loading in periodontal ligament cells and osteocytes and so on [26][27][28][29][30], and Stat3 in osteocytes was indicated to mediate osteogenic response to loading [29]. Others also demonstrated that load-induced bone formation may be increased by augmenting STAT3 signaling within osteocytes [31]. The osteoblastic STAT3 in BMSCs under mechanical force remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Such overproduction of osteoid is also observed histologically in VDR null mice bred on a normocalcemic diet ( 7,25,30 ) and in the context of human vitamin D–dependent rickets type 2. ( 38‐40 ) The use of multiple thresholds, including a specific threshold for low‐density bone, was essential for rapidly identifying this phenotype by MCT. This highlights another useful application of this new method previously applied to understand changes in cortical bone development ( 36,37 ) and the response of young bone to treadmill running activity.…”
Section: Discussionmentioning
confidence: 99%